Recent advances in engineering nanotopographic substrates for cell studies - Casanellas, Ignasi; Samitier, Josep; Lagunas, Anna (Frontiers in Bioengineering and Biotechnology, 2022)
Cells sense their environment through the cell membrane receptors. Interaction with extracellular ligands induces receptor clustering at the nanoscale, assembly of the signaling complexes in the cytosol and activation of downstream signaling pathways, regulating cell response. Nanoclusters of receptors can be further organized hierarchically in the cell membrane at the meso- and micro- levels to exert different biological functions. To study and guide cell response, cell culture substrates have been engineered with features that can interact with the cells at different scales, eliciting controlled cell responses. In particular, nanoscale features of 1-100 nm in size allow direct interaction between the material and single cell receptors and their nanoclusters. Since the first ‘contact guidance’ experiments on parallel microstructures, many other studies followed with increasing feature resolution and biological complexity. Here we present an overview of the advances in the field summarizing the biological scenario, substrate fabrication techniques and applications, highlighting the most recent developments.